Revision of the genus Stenolis Bates (Coleoptera, Cerambycidae, Lamiinae) - Monné, Miguel A. (Zootaxa, 2011)
The genus Stenolis Bates, 1864 is revised. New species described and illustrated include: Stenolis gilvolineata sp. nov., S. xanthostigma sp. nov., and S. giesberti sp. nov. from Panama; S. flavoguttata sp. nov. from Mexico (Veracruz and Chiapas); S. tavakiliani sp. nov. from Trinidad & Tobago, French Guiana, and Brazil (Amazonas and Rondônia); S. multimacula sp. nov. from Costa Rica S. marcelae sp. nov. from Brazil (Rondônia), Peru, and Bolivia; and S. nearnsi sp. nov. from Brazil (Amazonas and Pará). New transfers proposed: Lepturges circumscripta (Bates, 1881) comb. nov. from Stenolis, and S. vigintiguttata (Bates, 1885) comb. nov. from Nyssodrysternum. New synonyms proposed include: Nyssodrys decemguttata Bates, 1885 and Nyssodrys calligramma var. consobrina Melzer, 1934 = Stenolis calligramma (Bates, 1872). New country records: S. angulata (Fabricius, 1801) from Ecuador and Bolivia, S. calligramma (Bates, 1872) from Venezuela and Ecuador, and S. theobromae (Lara & Shenefelt, 1964) from Panama. A key for species identification is provided.